Development and validation of an instrument for procedure-related death notification - Orr, Frances Kate (My University, 2018)
Anaesthesia-related mortality is an important, potentially avoidable cause of perioperative mortality. A procedure-related death notification (PRDN) instrument is completed by relevant medical practitioners after an anaesthetic death and is used to audit practice and identify areas of care which need improvement. It is also used in medico-legal investigations when establishing cause of death and in the case of litigation. The current South African procedure-related death notification instrument, the GW 7/24 form, is considered to be outdated, inadequate and in need of revision. The aim of this study was to develop and validate a new PRDN instrument using Lynn’s two-stage model. During the Development stage a thorough literature review was done and items were generated to create a provisional PRDN instrument. This instrument was reviewed in a peer group discussion consisting of six local experts. Each item was debated until complete consensus was reached and experts were encouraged to make suggestions for the inclusion of additional items. During the Judgment-Quantification stage the revised PRDN instrument was emailed to 10 national experts for review. Each item was rated according to a 4-point Likert scale, with one being unimportant and four being important and succinct. The content validity of each item and of the instrument as a whole was then established by using the content validity index (CVI). The revised PRDN instrument achieved a CVI of 0.96 making it content valid, however, it was decided to improve upon this instrument even further. The national experts made several useful comments and suggestions which were taken into consideration and incorporated into a final PRDN instrument. This instrument was then re-rated by the national experts and achieved a CVI of 1. The final PRDN instrument is a validated, comprehensive form which could be used in place of the outdated GW 7/24 form in cases of procedure-related deaths.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in Anaesthesiology. Johannesburg, 2018